2021
DOI: 10.21037/tlcr-21-223
|View full text |Cite
|
Sign up to set email alerts
|

A signature of estimate-stromal-immune score-based genes associated with the prognosis of lung adenocarcinoma

Abstract: Background: Immune and stromal component evaluation is necessary to establish accurate prognostic markers for the prediction of clinical outcomes in lung adenocarcinoma (LUAD). We aimed to develop a gene signature based on the Estimation of STromal and Immune cells in MAlignant Tumor tissues using Expression data (ESTIMATE)-stromal-immune score in LUAD. Methods:The transcriptomic profiles of patients with LUAD were obtained from The Cancer Genome Atlas (TCGA), and the immune and stromal scores were derived usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…To apply it in clinical practice, we sought to construct a prognostic signature for gastric cancer based on ESTIMATE scores. Similar approaches have been applied in studies on different types of cancer ( Ding Q. et al, 2020 ; Meng et al, 2020 ; Ma et al, 2021 ). After constructing the PPI network using the genes in the intersection between high stromal and immune score related DEGs, we identified 9 hub genes in the CXCL12 module, including COL3A1, DDR2, ECM2, EDNRA, FOXF1, ISLR, PDGRB, SPON1, and TNFSF4.…”
Section: Discussionmentioning
confidence: 99%
“…To apply it in clinical practice, we sought to construct a prognostic signature for gastric cancer based on ESTIMATE scores. Similar approaches have been applied in studies on different types of cancer ( Ding Q. et al, 2020 ; Meng et al, 2020 ; Ma et al, 2021 ). After constructing the PPI network using the genes in the intersection between high stromal and immune score related DEGs, we identified 9 hub genes in the CXCL12 module, including COL3A1, DDR2, ECM2, EDNRA, FOXF1, ISLR, PDGRB, SPON1, and TNFSF4.…”
Section: Discussionmentioning
confidence: 99%
“…To further reveal the possible mechanism of the relationship between AFF3 expression and clinical characteristics of GC patients, we analyzed its relationship with immune cell infiltration in GC. Accumulated evidence has illustrated that stromal and immune scores are related to prognosis and the infiltration of the immune cell in various cancers 19,25–27 . Accordingly, to evaluate the effect of AFF3 on the prognosis and TME, we assessed the association between ESTIMATE score and AFF3 expression, which showed a positive relation between AFF3 and stromal/immune/estimate score (Figure 6A–C).…”
Section: Resultsmentioning
confidence: 99%
“…Accumulated evidence has illustrated that stromal and immune scores are related to prognosis and the infiltration of the immune cell in various cancers. 19 , 25 , 26 , 27 Accordingly, to evaluate the effect of AFF3 on the prognosis and TME, we assessed the association between ESTIMATE score and AFF3 expression, which showed a positive relation between AFF3 and stromal/immune/estimate score (Figure 6A–C ). These findings demonstrated that AFF3 expression might affect the prognosis of GC and potentially regulate the infiltration of immune cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated ESTIMATEScore, ImmuneScore, StromalScore, and TumorPurity using the ESTIMATE algorithm ( Ma et al, 2021 ). The TIMER algorithm was used to evaluate tumour infiltration of 6 immune cell types ( Li et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%